Extracellular Vesicles: Recent Insights Into the Interaction Between Host and Pathogenic Bacteria - Zou, Chaoyu; Zhang, Yige; Liu, Huan; Wu, Yu; Zhou, Xikun (Frontiers in Immunology, 2022)
Extracellular vesicles (EVs) are nanosized lipid particles released by virtually every living cell. EVs carry bioactive molecules, shuttle from cells to cells and transduce signals, regulating cell growth and metabolism. Pathogenic bacteria can cause serious infections via a wide range of strategies, and host immune systems also develop extremely complex adaptations to counteract bacterial infections. As notable carriers, EVs take part in the interaction between the host and bacteria in several approaches. For host cells, several strategies have been developed to resist bacteria via EVs, including expelling damaged membranes and bacteria, neutralizing toxins, triggering innate immune responses and provoking adaptive immune responses in nearly the whole body. For bacteria, EVs function as vehicles to deliver toxins and contribute to immune escape. Due to their crucial functions, EVs have great application potential in vaccines, diagnosis and treatments. In the present review, we highlight the most recent advances, application potential and remaining challenges in understanding EVs in the interaction between the host and bacteria.